The feasibility and added value of indocyanine green tracing in guiding sentinel lymph node biopsy for breast cancer - Ercument Gurluler; Volkan Polatkan; Kazim Senol; Mustafa Sehsuvar Gokgoz (Asian Journal of Surgery)
Objective: To compare the effectiveness of combined (indocyanine green [ICG]+ blue dye) tracing versus blue dye alone in guiding sentinel lymph node biopsy (SLNB) in breast cancer. Methods: A total of 112 female patients (mean ± SD age: 51.9 ± 11.9 years) with clinically node-negative (cN0) early-stage breast cancer were evaluated based on SLN tracing technique including methylene blue + ICG (n = 17), isosulfan blue + ICG (n = 19) and methylene blue alone (n = 76). Mapping patterns of each SLN, the number of total lymph nodes (TLNs) removed, including metastatic and hyperplastic lymph nodes, and the metastatic lymph node detection rate were analyzed for each tracing technique. Results: SLN detection rate was 100 % with complementary use of ICG. No significant difference was noted between methylene blue + ICG, isosulfan + ICG and methylene blue alone groups in terms of the mean ± SD number of TLNs removed (3.9 ± 2.5, 4.7 ± 3 and 3.7 ± 2.3, respectively) and metastatic lymph node detection rates (16.0 %, 16.25 % and 13.98 %, respectively). Complementary use of ICG revealed the N0 stage for 66.6 % of cases considered as Nx (cannot be detected) on blue dye alone. Also, 20.0 % of N0 and 11.1 % of N1 cases on blue dye were diagnosed with more advance nodal status (N1 and N2 respectively) after complementary use of ICG. Conclusions: The combined tracing (ICG + blue dye) seems valuable not only in terms of the SLN detection rates and lymph node yield but also has an added value in providing more accurate nodal stating and thus a proper final tumor staging with considerable therapeutic implications.